“Seniors of India’’: Life and Legacy. “Understanding Aging Trends and Implications” - Verma, Khushi (Magyar Gerontológia, 2024)
Our study set out to ascertain the significance of attending to the social, economic, and humanitarian needs of the aged. India has a great deal of responsibility to address the needs of older individuals because it is predicted to have the largest percentage of older adults in the world in the near future.